â€œANALYSIS OF HEADWAY TIME DISTRIBUTION AND VEHICLE GAPâ€ (Case studi intersection 3 muara badak kutai kartanegara) - JAYA, IRFAN (KURVA S JURNAL MAHASISWA, 2018)
Traffic is a means of moving from one place to another. Therefore traffic is an important problem. If traffic flow is disrupted or congestion occurs. The mobility of the community will also experience disruption. These disturbances will have a negative impact on the surrounding community.This research took place at intersection 3 muara badak kabupaten kutai kartanegara. Calculation analysis using travel time method. travel clock method and headway method to calculate headway time distribution.Based on the calculation of the maximum headway time of fourâ€“wheeled vehicles at the intersections samarinda-bontang it reaches 2.69 seconds and the average is 20 minutes for 1 hour, maximum time headway for four-wheeled vehicles at intersections muara badak-samarinda it reaches 2.38 seconds and the average is 20 minutes for1 hour, maximum time headway for four-wheeled vehicles at intersections bontang-muara badak it reaches 4.9 seconds and the average is 20 minutes for 1 hour.From these calculation it can beÂ  concluded in the medium category.